2003
DOI: 10.1021/jo026883p
|View full text |Cite
|
Sign up to set email alerts
|

Bridged Triarylamines:  A New Class of Heterohelicenes

Abstract: A series of bridged triarylamines, which constitute a new class of heterohelicenes, have been synthesized using a simple three-step procedure. These compounds are shown to be highly luminescent chromophores and are capable of being oxidized. The solid-state structures of these helicenes show a tendency for pi-stacking interactions into an overall zigzag motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 34 publications
0
95
0
Order By: Relevance
“…Although an increase in the number of ortho annulated rings generally leads to an increase in the racemization time and conformational stability, some tetracyclic compounds exhibit an unusually high thermal conformational stability. 52,[55][56][57] A comprehensive study of the circular dichroism properties of monoaza[5]helicenes was conducted by Caronna et al 61,62 It was observed that although the studied compounds showed similar features to the parent [5]helicene, all of them had shorter racemization time and showed distinct features due to the presence of the nitrogen atom. Ihmels and coworkers 63 showed that diazonia derivatives 46, 47 and 48 have a high binding selectivity for triple-helical DNA, most probably due to their double charge and helical molecular shape.…”
Section: Propertiesmentioning
confidence: 99%
“…Although an increase in the number of ortho annulated rings generally leads to an increase in the racemization time and conformational stability, some tetracyclic compounds exhibit an unusually high thermal conformational stability. 52,[55][56][57] A comprehensive study of the circular dichroism properties of monoaza[5]helicenes was conducted by Caronna et al 61,62 It was observed that although the studied compounds showed similar features to the parent [5]helicene, all of them had shorter racemization time and showed distinct features due to the presence of the nitrogen atom. Ihmels and coworkers 63 showed that diazonia derivatives 46, 47 and 48 have a high binding selectivity for triple-helical DNA, most probably due to their double charge and helical molecular shape.…”
Section: Propertiesmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Nonphotochemical syntheses of enantiopure [n]helicenes with n 7 have been reported. [3,[5][6][7][8][9][10] Many of these asymmetric syntheses have been based on the resolution of the racemic derivatives with a chiral auxiliary. [3, 10a] The development of a new asymmetric synthesis of enantiopure [n]helicenes, with adequate functionalization for both efficient homologation to extended helicenes and good solubility, is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, new synthetic methods that circumvented the problems often related with the classical photocyclization of stilbenes, [5] including Diels-Alder reactions, [6] cyclotrimerization of alkynes, [7] carbenoid couplings, [8] radical cyclizations, [9] Pd-mediated methodologies, [10] and olefin metathesis [11] were developed. Recently, bridged triarylamine heterohelicenes of the type 1-3 have been prepared [12, 13] and studied [13, 14] in the belief that the introduction of molecular helicity, sterically driven by the increasing overlap of the terminal a and b aryl rings, influences [2b] the well known photochemical and physical properties of triarylamines. [15] As a continuation of our efforts related to sulfur heterocycles chemistry, [16] we focused on compound 3, which was prepared by building the triarylamine skeleton by employing a Buchwald-Hartwig type cross-coupling of an open iodo-aniline in the final step of a multistep reaction sequence.…”
mentioning
confidence: 99%